KEMAMPUAN SISWA SLTP MEDAN DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA - Rusminah Kasma (Jurnal Kependidikan, 2003)
Abstract The purpose of this research is to obtain the description about the state SLTP students’ abilities in Medan in doing the mathematical story problem which is observed from problem solving phrase. The population is all the first year of state SLTP students in Medan, while the sample is gotten by stratified random sampling so there is 3 schools with 125 respondents. The data are analyzed by using descriptive analysis. The result shows that the first year os the state SLTP students’ ability in Medan in doing mathematical story problem are only 41.83%. the students ability in doing the mathematical story problem, observed from the problem solving phrases are (1) Phrase 1, understanding the problem 50.56%, (2) Phrase 2, Devising the solving plan 42.78% and 45.88%, (3) Phase 3, Carrying out the solving plan 35.55% and 56.25% and (4) Phrase 4, Looking back the result 24.44% and 51.45%. Keywords: mathematical story